CDKN2A testing and genetic counseling promote reductions in objectively measured sun exposure one year later - Stump, Tammy K. (Genet Med, 2019)
PURPOSE: This study investigated whether genetic counseling and test reporting for the highly-penetrant CDKN2A melanoma predisposition gene promoted decreases in sun exposure. METHOD: A prospective, non-equivalent control group design compared unaffected participants (N=128, M(age)=35.24, 52% men) from: 1) families known to carry a CDKN2A mutation, who received counseling about management recommendations and a positive or negative genetic test result, and 2) “no-test control” families known not to carry a CDKN2A mutation, who received equivalent counseling based on their comparable family history. Changes in daily UVR exposure (joules/m(2)), skin pigmentation (Melanin Index), and sunburns between baseline and one year following counseling were compared among carriers (n=32), noncarriers (n=46), and no-test control participants (n=50). RESULTS: Both carriers and no-test control participants exhibited a decrease one year later in daily UVR dose (Bs=−.52, −.33, ps<.01). Only carriers exhibited a significant decrease in skin pigmentation at the wrist one year later (B=−.11, p< .001), and both carriers and no-test control participants reported fewer sunburns than noncarriers (ps<.05). Facial pigmentation did not change for any group. Noncarriers did not change on any measure of UVR exposure. CONCLUSIONS: These findings support the clinical utility of disclosing CDKN2A test results and providing risk-management education to high-risk individuals.